A GNSS-free navigation strategy for orchards - Durand-Petiteville, A.; Cadenat, V.; Araújo, A. F. R.; Herbulot, A.; Villemazet, A.; Silva, A. F. L. A. da; Riou, C. (Anais do Congresso Brasileiro de Agroinformática (SBIAGRO), 2023)
This paper proposes a GNSS-free strategy allowing a robot to navigate through orchards autonomously. It relies on a perception system made of four cameras arranged to enlarge the robot’s field of view. Thanks to this choice, it becomes possible to perform complete navigation (both alley crossing and headland maneuvers) using only visual data, thus increasing the task’s robustness. Results validate the proposed strategy.